Pengaruh Inovasi Produk dan E-Commerce terhadap Keunggulan Bersaing : Survei pada Konsumen Produk B.O.T Store Kota Tasikmalaya - Acep Iwan Wahyudi (CV. Ulil Albab Corp, 2022)
The objectives of this research were find out and analyse the innovation product, e-commerce and competitive advantage on product of B.O.T Store Tasikmalaya, and the influence of the innovation product and e-commerce to competitive advantage on product of B.O.T Store Tasikmalaya. The research method used in this research are survey methods, data used in this research are primary and secondary data. The object of this research was consumers of product B.O.T Store Tasikmalaya, with using purposive sampling method. Analysis technique used Multiple Regression Analysis. The results proved that a the innovation product and e-commerce to influence competitive advantage on product of B.O.T Store Tasikmalaya.